1986
DOI: 10.1007/bf00454884
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effects of Cyclosporin on diabetes in NOD mice

Abstract: Non-obese diabetic mice aged 30 to 60 days were treated orally with Cyclosporin at doses of 25, 15 and 2.5 mg/kg every 2 days until 160 days of age. Diabetes developed in 12 out of 18 oil-treated mice (67%), with partial to complete Langerhans' islet destruction associated with lymphocytic infiltration. The non-obese diabetic mice showed a plasma glucose concentration of 6.62 +/- 0.92 mmol/l (mean +/- SD) at 50 days of age. The plasma glucose level of oil-treated non-obese diabetic mice gradually increased aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0
1

Year Published

1987
1987
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(49 citation statements)
references
References 7 publications
1
47
0
1
Order By: Relevance
“…The effect of fusidin in these three models of human type 1 diabetes was particularly encouraging for possible translation to the clinical setting, as inhibition of diabetes development in all these models is not achieved by the T-cell immunosuppressant CyA, which has shown a moderate effect in patients with type 1 diabetes [1]. In fact, whilst CyA prevents disease development in the NOD mouse [17] and the DP-BB rat [18], it worsens the course of the disease in the murine model of MLDSZ-induced diabetes [19].…”
Section: Discussionmentioning
confidence: 96%
“…The effect of fusidin in these three models of human type 1 diabetes was particularly encouraging for possible translation to the clinical setting, as inhibition of diabetes development in all these models is not achieved by the T-cell immunosuppressant CyA, which has shown a moderate effect in patients with type 1 diabetes [1]. In fact, whilst CyA prevents disease development in the NOD mouse [17] and the DP-BB rat [18], it worsens the course of the disease in the murine model of MLDSZ-induced diabetes [19].…”
Section: Discussionmentioning
confidence: 96%
“…Between 5 and 30% of adults presenting with mild hyperglycemia suggestive of type 2 diabetes may actually have a slowprogressive form of type 1 diabetes designated latent autoimmune diabetes of adults (Casteels et al, 1998). Immunosuppressive agents prevent the onset of type 1 diabetes in NOD mice and humans (Mori et al, 1986;Mahon et al, 1993;Casteels et al, 1998;Tabatabaie et al, 2000;Shapiro et al, 2002). Most of these agents have been studied in a prophylactic context, before the appearance of overt diabetes or insulitis (Mori et al, 1986;Mahon et al, 1993;Casteels et al, Article, publication date, and citation information can be found at http://jpet.aspetjournals.org.…”
Section: Introductionmentioning
confidence: 99%
“…Insulitis is noticed at clinical onset of the disease [1], particularly in patients younger than 15 years [2], and found to contain a mixture of reactive lymphocytes [3]. A form of insulitis was also detected in rodents developing autoimmune diabetes [4]. In (pre)diabetic non-obese diabetic mice (NOD), infiltrating lymphocytes and macrophages were shown to produce cytokines [5,6,7,8] that can destroy pancreatic beta cells in vitro [9,10].…”
Section: Introductionmentioning
confidence: 99%